Kajian Literatur : Pemanfaatan Mikroorganisme Termofilik dari Limbah Pertanian di Pulau Nias untuk Produksi Kompos Berkualitas Tinggi - Gulo, Beni Terima; Lase, Natalia Kristiani (Hidroponik : Jurnal Ilmu Pertanian Dan Teknologi Dalam Ilmu Tanaman, 2025)
One of the solutions for waste sustainability is the production of compositions of the highest quality from agriculture. Thermophilic microorganisms play an important role in accelerating the decomposition process and improving composition quality. The purpose of this article is to assess the potential of thermophilic microorganisms from Nias Island agricultural waste in compositional manufacturing based on existing literature. This research examines the role of thermophilic microorganisms such as Bacillus, Thermus, and Actinobacteria species in the decomposition of organic matter. This article also discusses microbiological strategies to improve soil health, thermophilic microorganisms in the composting process, the potential of agricultural waste on Nias Island.